Q: Solve this equation using subtitution x plus 7y equals 39 and 3x subtract 2y equals 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Subtract two from both sides and you are left with X equals -5

Set up the equation and solve: 13 = 7 + s (next subtract 7 from each side of the equation to solve for s) 6 = s

First, subtract 3x from each side of the equation. Then, divide each side of the equation by 7 .

Set up the equation and solve: x + 5 = -13 (next subtract 5 from each side of the equation to solve for x) x = -18

Here are the steps: -- Write the equation. -- Subtract 7 from each side of the equation. -- Subtract 4x from each side. -- Divide each side by 5.

Related questions

1

U can subtract 18 from each side of the equation.

Subtract two from both sides and you are left with X equals -5

Set up the equation and solve: 13 = 7 + s (next subtract 7 from each side of the equation to solve for s) 6 = s

First, subtract 3x from each side of the equation. Then, divide each side of the equation by 7 .

Set up the equation and solve: x + 5 = -13 (next subtract 5 from each side of the equation to solve for x) x = -18

Here are the steps: -- Write the equation. -- Subtract 7 from each side of the equation. -- Subtract 4x from each side. -- Divide each side by 5.

y=4x=1Because:8x - y = 45x + 3y = 17You can rearrange the first equation to give:y = 8x - 4And substitute this into the second equation:5x + 3(8x - 4) = 17Expanded out:5x + 24x - 12 = 1729x - 12= 1729x = 29So x=1And because you know know x you can put that into an equation to find y:y = 8x - 4y= 8 - 4y= 4

x=1, y=1

You can first subtract 2 from 12 to get 10. Then when you bring 10 across the = sign, it becomes -10, so 42-10 is 32.

h+1.5=8.4 subtract 1.5 from both sides h=6.9

19 = f + 5 Subtract 5 from both sides: 14 = f